Andropause and menopause – two sides of the same problem - Mędraś, Marek (Menopause Review/Przegląd Menopauzalny, 2002)
The andropause is an important problem of women. These biological phenomenon influences on comfort life of whole family. The author presents a problem of the andropause, that is a complex of symptoms occurring in men turning 50, resulting mainly from the gradual lowering of secretion of the testosterone, but also of the growth hormone (IGF-1), DHEAS or melatonin. It has to be noticed that the coined term „Andropause” is most unfortunate (a direct and simple acronym of „menopause”) and does not reflect the complex biological environment. Still a hypogonadism of the „male climacterium” may contribute to the development of an osteopenia (or osteoporosis), intensification of atherogensis, obesity, deterioration of the hematopoesis, disturbances in fibrinolysis, water balance and electrolyte equilibrium, lowering of spermatogenesis, deterioration of a libido and insulin resistance with all its consequences. Such relations are far from being direct or obvious. The emphasis is laid on the particularly essential – may be even a key – role of the genetic predispositions as well as of a style of life, adverse environmental influences, diet, addictions, etc. The most frequent symptoms of andropause are: nervosity, dysmnesia, impaired associative abilities, sleep disorders, increased fatigability, depressive tendencies, dizziness and headaches, cryohypersensitivity, heat strokes, supraventricular tachycardia, weakening of the muscle strength and mass, growth of the visceral fatty tissue, gynecomastia, osteo-, gonado- and arthrodynia. In effect they all constitute a psycho-endocrinological syndrome, with the symptoms swiftly withdrawing after a substitute therapy. If such an improvement is not observed, the underlying reason must be of another nature, e.g. depression. Hence the andropause in the exact meaning of this word does not occur, but it is just to recognize it as a biological phenomenon occurring in some of the men and the introduction of the properly managed hormone substitute therapy as rational. It’s very important from the point of view of the quality of family’s life.